Geographic and temporal patterns of non-lethal attacks on humpback whales by killer whales in the eastern South Pacific and the Antarctic Peninsula - Capella, Juan J.; Felix, Fernando; Florez-Gonzalez, Lilian; Gibbons Escobar, Jorge Eduardo; Haase, Ben; Guzman, Hector M. (My University, 2018)
The role and impact of killer whales Orcinus orca as predators of baleen whales has been emphasized by studies of humpback whales Megaptera novaeangliae. In this study, rake marks on the fluke were used as a proxy for predatory attacks in a sample of 2909 adult humpback whales and 133 calves from 5 breeding and 2 feeding locations in the eastern South Pacific and the Antarctic Peninsula. The goal of this study was to evaluate how often, at what age, where, and when humpback whales were more susceptible to attacks. Overall, 11.5 % of adults and 19.5 % of calves had rake marks on their flukes. Significant differences were found in the prevalence of scars in calves when comparing breeding (9 %) vs. feeding areas (34 %) (chi(2) = 10.23, p < 0.01). Multi-year sighting analysis of scar acquisition in 120 adults (82 % site fidelity) and 37 calves in the Magellan Strait showed no new marks after the initial sighting for the subsequent 15 yr. This finding indicates that rake marks were most probably acquired when whales were calves, which supports the belief that scar acquisition is a once in a lifetime event. The odds of having rake marks increased with time but with a significantly higher rate in calves (chi(2) = 5.04, p < 0.05), which suggests an increase in predation pressure over time. Our results support the earlier hypothesis that killer whale attacks occur mostly on calves, near breeding sites, and during the first migration to feeding areas.
Keywords: non-lethal attacks; eastern south pacific; migration; humpback whale; megaptera novaeangliae; killer whale; orcinus orca; rake scars